Germinação e vigor de sementes de feijão comum em condição de submersão em água - Vieira, Geraldo Henrique Martins (2012)
The work was performed at the Laboratory of Seed Analysis at the University of the West Paulista (UNOESTE) Presidente Prudente - SP, with cultivars of common bean (Phaseolus vulgaris L.), Pearl, Pee-wit IPR and IPR 139, aimed to analyze the loss of germination condition and vigor of anoxia, by submersion in deionized water for periods of 0,1,2,4,8 and 16 hours at 25°C. The test was conducted with four replications of 50 seeds per lot being evaluated on criteria seeds germination, vigor, root length and shoot length, total dry weight of roots and shoots, total dry matter, electrical conductivity. The loss of germination and vigor is directly proportional to the immersion time. The one-hour period of immersion is sufficient to begin to appear germination differences among cultivars. The cultivar IPR-139 showed up as the cultivar most susceptible to damage caused by submersion, and recommended its use in soils with good drainage. Cultivars IPR-Tiziu and Pérola showed up as being less susceptible to damage caused by submersion. The soaking is quick at the start of immersion until the four-hour period (phase I) from which starts the stationary phase imbibition (phase II). The cultivars that lose less electrolytes to the solution of imbibition are more tolerant to submergence in water.